Odpowiedź :
Zadanie 8 :
(a - b)² + 4ab = (a + b)²
L = a² - 2ab + b² + 4ab = a² + 2ab + b²
P = (a + b)² = a² + 2ab + b²
L = P
C. N. D.
Zadanie 9 :
(a + b)²(a - b) = (a² - b²)(a + b)
L = (a + b)²(a - b)
P = (a - b)(a + b)(a + b) = (a + b)²(a - b)
L = P
C. N. D.
Odpowiedź:
8)
(a - b)² + 4ab = (a +b)²
L = a² - 2ab + b² + 4ab = a² + 2ab + b²
P = (a + b)² = a² + 2ab + b²
L = P
9)
( a + b)²(a - b) = (a² - b²)(a + b)
L = (a + b)² (a - b ) = (a² + 2ab + b²) ( a - b) = a³ - a²b + 2a²b - 2ab² +ab² - b³ = a³ +a²b - ab² - b³
P = (a² - b²) (a + b) = a³ + a²b - ab² - b³
L = P
Szczegółowe wyjaśnienie:
Wymnażam kolejno wszystkie wyrażenia i sprawdzam ,czy lewa strona równa się prawej .